Kebebasan Pers di Indonesia - Metalianda; Muhammad Japri; Iva Yulia Munawarah; I Nyoman S; Romiansyah (LPPM STIH Awang Long, 2019)
Freedom of the Press is the freedom to use opinions, both written and oral, through press media, such as newspapers, magazines, and bulletins. The freedom of the press is one of the embodiment of the sovereignty of the people and is a very important element in the life of society, nation and democratic state. Therefore protection of press freedom, must be guaranteed by the state.